Childhood body size, adulthood adiposity, underlying mechanisms, and risk of incident hypertension: a prospective cohort study of 180,527 participants - Shujing Ma; Xue Liu; Ruilang Lin; Ye Yao; Min Zhao; Yongfu Yu; Costan G. Magnussen; Bo Xi (BMC Medicine)
Abstract Background Mechanisms underlying the association of life-course adiposity with incident hypertension in adulthood have not been comprehensively investigated. In this study, we aimed to investigate the potential biochemical and metabolomic mechanisms underlying the association between adiposity and incident hypertension. Methods A total of 180,527 participants from the UK Biobank aged 37 to 73 years were included. Associations of childhood body size or adulthood adiposity status as well as child–adult weight status change with incident adulthood hypertension were estimated by multivariate Cox proportional regression models. Results Participants with childhood thinner body size and adulthood obesity had the highest risk of incident hypertension (hazard ratio, HR = 3.09, 95% CI = 2.88–3.32) compared with those with “average → normal” pattern, followed by those with “average → obese” pattern (HR = 2.45, 95% CI = 2.31–2.61) and “plumper → obese” pattern (HR = 2.82, 95% CI = 2.62–3.02). Of note, those with “plumper → normal” pattern (HR = 1.11, 95% CI = 1.00–1.23) and “thinner → normal” pattern (HR = 1.17, 95% CI = 1.10–1.24) had the second and third lowest risk of incident hypertension. Adulthood overweight (mediation proportion: 58.7%, 95% CI: 40.4–74.8%) or obesity (mediation proportion = 46.7%, 95% CI: 29.4–64.9%) largely mediated the association between childhood plumper body size and hypertension. The association between adiposity and hypertension was mediated by biochemical indices (e.g., liver function, immunometabolism) and metabolites (e.g., alanine aminotransferase, apolipoprotein A) (mediation proportions ranging from 3.2 to 23.4%). Conclusions Thinner or plumper body size in childhood increases the risk of incident adulthood hypertension, and adulthood adiposity partly mediated this association, suggesting the importance of maintaining normal weight across the life course. Several biochemical indices and metabolites mediated these associations providing clues to underlying biological mechanisms.